The Kansas State Seal - Weekly Atchison Champion (Symphony in the Flint Hills, 2019)
Introduction: The State Seal is at last agreed upon, if no unforeseen circumstance should arise to change the minds of members. The House some-time since adopted a device, for which, when the resolution came up the Senate substituted another. (Reprinted from: The Weekly Atchison Champion, Atchison, KS 25 May 1861.)